How to select a Supply Chain Finance solution?. Issue 4 (October 2021) - Guida, Michela; Moretto, Antonella Maria; Angelo Caniato, Federico Francesco
Abstract: In the complex picture of Supply Chain Finance (SCF), there is still a need for a model supporting managerial decisions in selecting the most suitable financing solution. The objective of the presented exploratory work is to bring together the relational aspects between buyers and suppliers, and the characteristics of SCF solutions. Based on expert interviews and a focus group, the main result consists of a classification model of buyer-led SCF solutions, according to the characteristics of the relationship between a buyer and its suppliers, in terms of bargaining power and cumulative transaction value. The model thus describes the logics behind the adoption by a buyer firm of one or more SCF solutions to be implemented with different suppliers. Highlights: We develop a decision support model for the adoption of buyer-led Supply Chain Finance (SCF) solutions. We investigate 6 SCF solutions from the buyer perspective, through expert interviews and a focus group. We combine the characteristics of SCF solutions with the relational aspects between buyers and suppliers. Buyer-led SCF solutions are selected according to the bargaining power of the parties and cumulative transaction value. The solutions are placed on a four-quadrant matrix showing the most suitable one based on the buyer-supplier relationship.